The Relationship Between Ages, Duration of Stay and the Number of Households on Community Readiness to Face Floods in Kelantan - Mehat, Nurul Aini; Syed Hussain, Tuan Pah Rokiah (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2018)
Previous studies have failed to relate the factors of knowledge, experience, and opinions with the aspects of readiness within the community from the perspective of age, duration of stay and the number of households in the flood basin area. Meanwhile, the scope of this study is a basis for the authorities to determine the relating to flooding in certain areas. The objective of the study is to determine the relationship between the age, duration of stay, and the number of households with community readiness from the cognitive aspects to face the flood disaster. The study involved two areas of Kota Bharu and Kuala Krai. A survey was conducted on 383 respondents using a convenience sample technique. The result of the study shows that the younger the respondent; the better the awareness of flood-related knowledge; the newer the respondent living in an area; the better the awareness of flood-related knowledge, the fewer the people in the household in a family, the better the awareness of flood-related aspects and experience, the newer the duration of one respondent; the better the awareness of flood-related aspects and opinion. The results as a whole show that in the context of a relationship, tests found that respondents' knowledge of flood-related disasters is determined by age and duration of stay only, but the number of the households does not affect a person's knowledge. In the context of the respondents' experience of facing flood disaster, it is only determined by the number of households; while the respondents' opinion is only determined by the duration of their staying